Established companies diversifying into young industries: A comparison of firms with different levels of performance - Smith, Clayton G.; Cooper, Arnold C. (Strategic Management Journal, 1988)
Abstract Differences in performance among established firms diversifying into young industries were investigated, with hypotheses concerning 11 ‘corporate level’ strategic and organizational variables being examined. Performance was found to be associated with firm size and financial strength, time of entry, and the maturity of the firm's markets. The importance of several variables examined also appears to change as an industry evolves.